Plasticity of adult human pancreatic duct cells by neurogenin3-mediated reprogramming. - Swales,N; Martens,GA; Bonné,S; Heremans,Y; Borup,R; Van,de Casteele M; Ling,Z; Pipeleers,D; Ravassard,P; Nielsen,F; Ferrer,J; Heimberg,H (PLOS One, 2012)
AIMS/HYPOTHESIS: Duct cells isolated from adult human pancreas can be reprogrammed to express islet beta cell genes by adenoviral transduction of the developmental transcription factor neurogenin3 (Ngn3). In this study we aimed to fully characterize the extent of this reprogramming and intended to improve it. METHODS: The extent of the Ngn3-mediated duct-to-endocrine cell reprogramming was measured employing genome wide mRNA profiling. By modulation of the Delta-Notch signaling or addition of pancreatic endocrine transcription factors Myt1, MafA and Pdx1 we intended to improve the reprogramming. RESULTS: Ngn3 stimulates duct cells to express a focused set of genes that are characteristic for islet endocrine cells and/or neural tissues. This neuro-endocrine shift however, is incomplete with less than 10% of full duct-to-endocrine reprogramming achieved. Transduction of exogenous Ngn3 activates endogenous Ngn3 suggesting auto-activation of this gene. Furthermore, pancreatic endocrine reprogramming of human duct cells can be moderately enhanced by inhibition of Delta-Notch signaling as well as by co-expressing the transcription factor Myt1, but not MafA and Pdx1. CONCLUSIONS/INTERPRETATION: The results provide further insight into the plasticity of adult human duct cells and suggest measurable routes to enhance Ngn3-mediated in vitro reprogramming protocols for regenerative beta cell therapy in diabetes.